TOWARDS INDUSTRY 5.0: A HUMAN-CENTRIC CYBER-PHYSICAL PRODUCTION SYSTEM FOR INDONESIA’S BATIK SMES - Mochammad Isa Anshori; Chai Pao; Siri Lek; Andy Rachman (Scientechno: Journal of Science and Technology, 2025)
Industry 4.0 has revolutionized manufacturing through automation and data exchange, but the transition towards Industry 5.0 emphasizes human-centric approaches, integrating human expertise with advanced technologies like cyber-physical systems (CPS). In Indonesia, Small and Medium Enterprises (SMEs), particularly in traditional sectors such as batik production, face challenges in adapting to these technological advancements. The batik industry, while rich in cultural heritage, has yet to fully embrace automation or digitalization, resulting in inefficiencies and limited scalability. This study aims to explore the potential of Industry 5.0 by developing a Human-Centric Cyber-Physical Production System (HCPPS) tailored to Indonesia’s batik SMEs. The goal is to enhance production efficiency while preserving traditional craftsmanship through the integration of smart technologies. The research employed a mixed-methods approach, combining qualitative interviews with batik producers and quantitative analysis using data from pilot implementations of a CPS model. A prototype of a human-centric cyber-physical system was developed, integrating Internet of Things (IoT) devices, augmented reality (AR), and robotics to assist batik artisans. The implementation of the HCPPS prototype resulted in a 25% increase in production efficiency, while artisans reported higher job satisfaction due to enhanced skill integration with technology. The system enabled greater customization, faster production cycles, and reduced errors. The study demonstrates that Industry 5.0’s human-centric approach can significantly improve productivity in traditional sectors like batik, providing a path for Indonesian SMEs to modernize while maintaining their cultural identity.